2014
DOI: 10.1093/ntr/ntu078
|View full text |Cite
|
Sign up to set email alerts
|

Carbonyl Compounds in Electronic Cigarette Vapors: Effects of Nicotine Solvent and Battery Output Voltage

Abstract: Vapors from EC contain toxic and carcinogenic carbonyl compounds. Both solvent and battery output voltage significantly affect levels of carbonyl compounds in EC vapors. High-voltage EC may expose users to high levels of carbonyl compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
585
4
26

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 632 publications
(644 citation statements)
references
References 16 publications
29
585
4
26
Order By: Relevance
“…Moreover, this study did not examine the effect of varying the e-liquid PG/VG ratio; prior studies have shown that manipulating the ratio affects the nicotine and carbonyl yields. 31,37 However, our main intention was not to investigate performance variation across products, but rather to illustrate the wide range of possible nicotine yields attainable even from a relatively constrained basis set. Our results show that even for a single ECIG brand, a single PG/VG ratio, and only five different user profiles, a 50-fold change in nicotine delivery is possible; a span that ranges from negligible amounts to several cigarettes worth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this study did not examine the effect of varying the e-liquid PG/VG ratio; prior studies have shown that manipulating the ratio affects the nicotine and carbonyl yields. 31,37 However, our main intention was not to investigate performance variation across products, but rather to illustrate the wide range of possible nicotine yields attainable even from a relatively constrained basis set. Our results show that even for a single ECIG brand, a single PG/VG ratio, and only five different user profiles, a 50-fold change in nicotine delivery is possible; a span that ranges from negligible amounts to several cigarettes worth.…”
Section: Discussionmentioning
confidence: 99%
“…In one recent study, carbonyl compounds measured in ECIG aerosol from 13 different nicotine solutions at 3.2 and 4.8 V were compared: solvent and output voltage significantly affect the amount of carbonyls in the aerosol. 31 Prior studies have also explored the toxicant emissions produced from different brands of ECIGs but few have varied voltage systematically (see Kosmider et al 31 ), and none have explored the influence of user topography. Goniewicz et al 12 measured the nicotine yield in aerosols generated from 16 different ECIG brands using an average puffing condition based on topography measurements of 10 ECIG users (1.8-s puff duration, 70-ml puff volume) and found that the nicotine yield in 15 puffs ranged from 0.025 to 0.77 mg, which is lower than the dose inhaled in one conventional cigarette.…”
Section: Introductionmentioning
confidence: 99%
“…More powerful e-cigarettes, commonly known as tank systems, heat nicotine liquid hot enough to produce cancer-causing carcinogens, such as formaldehyde and acetaldehyde, in their vapor. 3 Further, in a study of human bronchial cells that contained some mutations found in smokers at risk of lung cancer, scientists found a pattern of gene expression in cells grown in a medium exposed to ecigarette vapor that was similar to the pattern found in cells grown in a medium exposed to combustible tobacco smoke. 4 In addition, the virulence of drugresistant bacteria can be increased by e-cigarette vapors and affect the ability of cells to destroy bacteria.…”
Section: Balancing Benefits With Harmsmentioning
confidence: 90%
“…11 Both propylene glycol and glycerol decompose to form carcinogens formaldehyde and acetaldehyde depending on the voltage of the battery used in the e-cigarette. 12,13 An e-cigarette consists of a catridgec ontining a liquid, an atomizer which is a vaporization chamber with a heating element and a battery. Activation of the atomizer will heat the liquid and produces a vapor to inhale.…”
Section: Discussionmentioning
confidence: 99%